Dual roles of Drosophila p53 in cell death and cell differentiation. - Fan, Y.; Lee, T.V.; Xu, D.; Chen, Z.; Lamblin, A.F.; Steller, H.; Bergmann, A. (Cell Death and Differentiation, 2010)
The mammalian p53 family consists of p53, p63 and p73. Whereas p53 accounts for tumor suppression through cell-cycle arrest and apoptosis, the functions of p63 and p73 are more diverse and also include control of cell differentiation. The Drosophila genome contains only one p53 homolog, Dp53. Previous work has established that Drosophila p53 (Dp53) induces apoptosis, but not cell-cycle arrest. In this study, using the developing eye as a model, we show that Dp53-induced apoptosis is primarily dependent on the pro-apoptotic gene, head involution defective (hid), but not reaper (rpr), and occurs through the canonical apoptosis pathway. Importantly, similar to p63 and p73, expression of Dp53 also inhibits cellular differentiation of photoreceptor neurons and cone cells in the eye independently of its apoptotic function. Intriguingly, expression of the human cell-cycle inhibitor p21 or its Drosophila homolog dacapo (dap) can suppress both Dp53-induced cell death and differentiation defects in Drosophila eyes. These findings provide new insights into the pathways activated by Dp53 and reveal that Dp53 incorporates functions of multiple p53 family members.